‘Hamlet Without the Prince’ – The U.S. Supreme Court on Religious Practice: Changes in Case Law in the Light of the Kennedy v. Bremerton School District Case - Kovács, Helga (Public Governance, Administration and Finances Law Review, 2023)
The Supreme Court of the United States of America has recently issued a decision in several cases that are closely related to First Amendment rights. In doing so, the Court has changed its own set of criteria from its earlier practice. The reasons for these decisions have attracted increased interest among practitioners and academics, as it is a long time since the Court has so clearly distanced itself from its own precedent and called lower courts to account for failing to take certain criteria into account. By analysing the Court’s reasoning on the role of history and tradition and the compelling nature of religious belief, this paper seeks to answer the question whether the change in the Supreme Court’s practice can indeed be considered truly substantial. I argue that the change is significant, but as a process is not without precedent, and is not necessarily unacceptable in terms of its consequences.